Rational management of people in public organizations - Drozdowski, Grzegorz (Management and Administration Journal, 2023)
Rational management of people should not only be associated with economic organizations. It is also related to the functioning of public organizations. This is due to the fact that public organizations, in the sphere of personnel actions, must take into account changes in a rapidly changing environment. From this the conclusion that the rational management of human capital not only can, but must also apply to public organizations.